(untitled) (Bangladesh Journal of Medical Microbiology, 2017)
Patients colonized with Methicillin resistant Staphylococcus aureus (MRSA) in hospital are considered as one of the risk factors for infection with MRSA. Worldwide spread of MRSA in both hospital setting and community poses public health threat. This study was undertaken to determine the frequency of MRSA colonization among patients at time of hospital admission. Five hundred adult patients were screened within 24 hrs of admission in different wards in Dhaka Medical College Hospital by taking nasal swabs from anterior nares and were analyzed. All isolated Staphylococcusaureus were screened to detect methicillin resistance by modified Kirby-Bauer disc diffusion method using oxacillin and cefoxitin disc and then all MRSA isolates were subjected for MIC testing against oxacillin by agar dilution method and PCR for mecAgene detection. Out of 500 patients Staph aureus nasal colonization was observed among 112 (22.4%) patients and among those 7.6% was MRSA.MRSA colonization rate was 23.29% among patients who had history of prior hospitalization and was 4.92% among community residents who had no previous hospitalization history in last 12 month. A significant number of patients (7.6%) were colonized with MRSA at the time of admission. Screening for MRSA carriers among this population is necessary for hospital acquired infection control. Bangladesh J Med Microbiol 2014; 08 (02): 08-13